Physical symptoms distress and demoralization among haemodialysis patients; the mediating effect of spirituality and self-compassion. A cross-sectional questionnaire survey - Chia-Hui Lin; Yi-Chien Chiang; Wen-Yi Li; Tsung-Lan Chu; Ya-Chu Hsiao (International Journal of Nursing Studies Advances)
Background: Long-term haemodialysis patients often experience physical symptom distress (PSD) and varying levels of demoralization. Spirituality and self-compassion can help patients to cope these challenges. However, the interrelations between these variables remain underexplored, necessitating further investigation. Objectives: To examine the effect of PSD on demoralization among haemodialysis patients and to determine whether spirituality and self-compassion mediate these relationships. Design: A cross-sectional correlational study. Settings: A convenience sample was used to recruit from two haemodialysis clinics. Methods: Self-report questionnaires were the Physical Symptom Distress Scale, Demoralization Scale, Functional Assessment of Chronic Illness Therapy-Spiritual Well-Being Scale-12, and Self-Compassion Scale. Relationships and mediators were examined with Pearson's correlations and multiple linear regression analysis, respectively. Results: A total of 156 participants participated. Mean age of participants was 61.3 years (SD = 11.3). Most participants were male (66 %) and had received dialysis for ≥ 5 years (61.5 %). Pearson's correlation indicated higher scores for PSD were significantly associated with lower levels of spirituality and self-compassion and higher levels of demoralization. There was a significant total and direct effect of PSD on demoralization. Mediation analysis indicated that the relationship between PSD and demoralization was partially and significantly mediated by spirituality and self-compassion. Demoralization can be explained by 46.83 % variance accounted by these predictors in the mediation model. Conclusion: Long-term haemodialysis can cause chronic symptom distress and feelings of demoralization. The mediating effects of spirituality and self-compassion on PSD and demoralization suggest that these qualities may act as emotional regulators that enable haemodialysis patients to be more accepting of symptom distress, which results in lower levels of demoralization. Our findings imply that developing strategies to increase spirituality and self-compassion could help patients manage chronic symptom distress associated with haemodialysis, reduce demoralization, and ultimately improve their quality of life.